State administration of higher education in the Republic of Kazakhstan: problem and perspectives - Tapenova, G.S.; Bugubayeva, R.O.; Kupalova, G. (BUKETOV BUSINESS REVIEW, 2020)
Object: identify current problems of higher education in the Republic of Kazakhstan, aimed at improving the competitiveness of education, the development of human capital by ensuring the availability of quality education for sustainable economic growth. The article also discusses the current state and development trends of the higher education system in the Republic of Kazakhstan. Structure of higher and postgraduate education in the Republic of Kazakhstan. Data on the priority directions of development of the higher education system at the present stage, as well as the implementation of program goals and objectives defined in international and national strategic and program documents, are analyzed. Methods: the article uses theoretical and empirical research methods: the works of foreign and Kazakhstani authors on this topic, legislative and program documents are studied. In order to identify problems, an analysis of official statistics was conducted. Findings: the analysis and forecast of the faculty of the higher education system. Analysis of the dynamics of changes in the number of students in the higher education system of the Republic of Kazakhstan. The analysis of the ratio of students in the form of ownership of universities, the ratio of students in the form of payment for education, as well as the dynamics of the contingent of students in the regional context. Conclusions: as a result of the study, conclusions were drawn and development prospects and methods for improving the monitoring of higher education in the Republic of Kazakhstan were determinedю